Digital control systems theoretical problems and simulation tools - Veloni, Anastasia; Miridakis, Nikolaos (CRC Press, Taylor & Francis Group, 2018)
The objective of this book is to provide a collection of solved problems on control systems, with an emphasis on practical problems. Each chapter ends with a discussion on applying MATLAB®, LabVIEW, and/or Comprehensive Control to the previously introduced concepts. The solutions are based directly on math formulas given in extensive tables throughout the text.